Political News Construction: Media Efforts to Frame Public Discourse Related to 2024 Presidential Candidates in Tvonenews.com - Nurjanah, Yuyum; Nurhadi, Jatmika; Wiyanti, Sri (P3M Politeknik Negeri Media Kreatif, 2024)
This study aims to obtain a description of how tvonenews.com online media frames political news so that it can influence public opinion through news informed about the 2024 presidential candidate. This study utilizes Pan and Kosicki's analysis, with the research aspects being syntax, script, thematic, and rhetorical. The approach was conducted using a descriptive qualitative method. The results found that there are similarities and differences in the construction of the three news articles analyzed. The similarity of the three news lies in the script and thematic structure, each news is equipped with 5W+1H elements to form a coherent sentence. Meanwhile, the syntactic and rhetorical structures differ substantially, seen from the use of headlines, image selection, and word usage in the news.